Orbital-anisotropic electronic structure in the nonmagnetic state of BaFe2(As1−x P x )2 superconductors - T. Sonobe (Nature Portfolio, 2018)
Abstract High-temperature superconductivity in iron-pnictides/chalcogenides arises in balance with several electronic and lattice instabilities. Beside the antiferromagnetic order, the orbital anisotropy between Fe 3d xz and 3d yz occurs near the orthorhombic structural transition in several parent compounds. However, the extent of the survival of orbital anisotropy against the ion-substitution remains to be established. Here we report the composition (x) and temperature (T) dependences of the orbital anisotropy in the electronic structure of a BaFe2(As1−x P x )2 system by using angle-resolved photoemission spectroscopy. In the low-x regime, the orbital anisotropy starts to evolve on cooling from high temperatures above both antiferromagnetic and orthorhombic transitions. By increasing x, it is gradually suppressed and survives in the optimally doped regime. We find that the in-plane orbital anisotropy persists in a large area of the nonmagnetic phase, including the superconducting dome. These results suggest that the rotational symmetry-broken electronic state acts as the stage for superconductivity in BaFe2(As1−x P x )2.